COMMUNICATION STRATEGIES EMPLOYED BY EFL LEARNERS - Syahri, Indawan (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2009)
Communication strategies have something to do with ends and means. This current study attempts to answer the questions â€œWhat types of communication strategies were used by the speakers in speaking activities?â€ and â€œWhat were the functions of the communication strategies produced by the speakers in their interactions in performing the same tasks?â€ The investigation was conducted to the subjects taking Speaking Class at the English Study Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Palembang. The findings show that there were eleven types of communication strategies used by EFL learners in their interactions stimulated by the reading passages and pictures specifically utilized for data collection. Communication strategies were used by the speakers not only because of compensating for insufficient means, but also the need of communication.